2018
DOI: 10.17921/2447-8938.2018v20n2p106-111
|View full text |Cite
|
Sign up to set email alerts
|

Osteomuscular Symptoms in Dentists: a Pilot Study

Abstract: Dentists are more likely to develop occupational diseases due to the routine use of arms and shoulders with the same patterns of movement. Musculoskeletal disorders encompass several pathologies that are the main cause of early worker withdrawal and can lead to symptoms that hinder professional activity, such as pain, fatigue and even the spine functional impairment. The aim of this study was to evaluate the prevalence of musculoskeletal symptoms related to the dentists' professional activity. This is a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…We have verified that the greater risk of musculoskeletal injury presented a higher percentage at the level of the back, followed by the arms; in their study, de ODONTOLOGÍA ODONTOLOGÍA cols. 5 , encontraron que las regiones anatómicas que la mayoría de los profesionales informaron dolor fue en la parte baja de la espalda, el cuello, las manos, los hombros y la parte superior de la espalda. Dada la gravedad de los síntomas musculoesqueléticos y sus consecuencias en la salud de los dentistas, es fundamental adoptar prácticas que tengan como objetivo prevenir su aparición; ya que afecta directamente la calidad de vida del profesional 13 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…We have verified that the greater risk of musculoskeletal injury presented a higher percentage at the level of the back, followed by the arms; in their study, de ODONTOLOGÍA ODONTOLOGÍA cols. 5 , encontraron que las regiones anatómicas que la mayoría de los profesionales informaron dolor fue en la parte baja de la espalda, el cuello, las manos, los hombros y la parte superior de la espalda. Dada la gravedad de los síntomas musculoesqueléticos y sus consecuencias en la salud de los dentistas, es fundamental adoptar prácticas que tengan como objetivo prevenir su aparición; ya que afecta directamente la calidad de vida del profesional 13 .…”
Section: Discussionunclassified
“…La Norma ISO 11226, 'Ergonomía: evaluación de posturas estáticas de trabajo', proporciona posturas ideales para el trabajo dental, como sentarse en una postura activa, Oliveira and colls. 5 , found that the anatomical regions that most professionals reported pain was in the lower back, neck, hands, shoulders, and upper back. Given the severity of musculoskeletal symptoms and their consequences on the health of dentists, it is essential to adopt practices that aim to prevent their appearance; since it directly affects the quality of life of the professional 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations